A Orquestra dos Sonhos: proposta didática e atuação polifônica - Debora Andrade (2008)
The object studied in this research is "A Orquestra dos Sonhos", a chamber opera for chidren by the brazilian composer Tim Rescala. It is made of three acts and was written in 1996 with the intention of attracting the audience to the theatre. This is a qualitative study with two basic purposes. The first is to investigate the composing procedures applied by Rescala in this opera to establish comunication with the audience. The second, challenges that it imposes to the interpreter via polyphonic performance. Moreover, we present a brief biography of the composer and a catolog of his works. Data have been collected through systematic visits to the website of the composer, reading newspaper articles from his collection, mail between the composer and the researcher, questionaire sent to instrumentalists who participated in the execution of this opera in Rio de Janeiro in the year 1997, and the observation of its full-score and audio-visual recording.